2014
DOI: 10.1103/physreve.89.052702
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of polymer ejection from capsid

Abstract: Polymer ejection from a capsid through a nanoscale pore is an important biological process with relevance to modern biotechnology. Here, we study generic capsid ejection using Langevin dynamics. We show that even when the ejection takes place within the drift-dominated region there is a very high probability for the ejection process not to be completed. Introducing a small aligning force at the pore entrance enhances ejection dramatically. Such a pore asymmetry is a candidate for a mechanism by which viral eje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 43 publications
5
17
0
Order By: Relevance
“…Also the viscosity in their experiments is much larger than in our simulations. with previous findings [1][2][3][4][6][7][8][9], scaling τ ∼ N β 0 is obtained. Here, β = 1.362 ± 0.05, 1.325 ± 0.04, 1.293 ± 0.04, 1.299 ± 0.03, and 1.300 ± 0.04 for ρ 0 = 0.5, 0.75, 1, 1.25, and 1.5, respectively.…”
Section: The Computational Modelsupporting
confidence: 52%
See 1 more Smart Citation
“…Also the viscosity in their experiments is much larger than in our simulations. with previous findings [1][2][3][4][6][7][8][9], scaling τ ∼ N β 0 is obtained. Here, β = 1.362 ± 0.05, 1.325 ± 0.04, 1.293 ± 0.04, 1.299 ± 0.03, and 1.300 ± 0.04 for ρ 0 = 0.5, 0.75, 1, 1.25, and 1.5, respectively.…”
Section: The Computational Modelsupporting
confidence: 52%
“…An important class of such processes is the capsid ejection where a polymer is initially in a compact conformation inside a capsid and then ejects outside through a pore a few nanometers wide. By far the most important biological process of this class is the viral packaging in and ejection from bacteriophages [1][2][3][4][5][6][7][8][9]. The ejection of double-stranded (ds) DNA is clearly the most studied case.…”
Section: Introductionmentioning
confidence: 99%
“…Packaging and ejection of macromolecules in confinements are of high interest due to the potential technological and medical applications, such as drug delivery and gene therapy [1]. The basic understanding of these processes is important also due to the relevant fundamental biological processes, the most prominent of which is the viral packaging in and ejection from bacteriophages [2][3][4][5][6][7][8][9][10]. The theoretical treatments of polymer ejection are strictly based on fully flexible chains [2,8,9], in spite of the experimental studies being almost solely done on semiflexible double-stranded DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The ejection time was deduced to scale asymptotically asat the osmotic driven stage. Simulations, on the other hand, revealed that translocation behaviors can be altered by the details of the escape pore [16,17], the cavity [18,19], the solvent [20,21], the chain stiffness [19,22], etc. Despite of the varieties, universalities can be still traced.…”
mentioning
confidence: 99%